Increase Service Access Mental Health in Developing Countries: Literature Review Challenge and Solution Community Based (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
Mental health has become one of the major issues in social development, especially in developing countries, where challenges such as social stigma, lack of resources, and limited access to health services are major barriers. This study aims to explore mental health policies adopted in developing countries and the role of community based health services in supporting the implementation of such policies. The study used a literature review approach to research published in the last 10 years (2013-2023) to identify policies, challenges, and successes in addressing mental health. The results showed that the integration of mental health into primary health services, human resource capacity building, and community-based programs have a significant positive impact in improving access and quality of mental health services. Programs such as WHO's mhGAP, which strengthens the capacity of primary health services to treat mental disorders, have been successfully adopted by developing countries such as Ethiopia, Uganda, and Nepal. In addition, community-based approaches involving the training of mental health cadres have been shown to be effective in detecting and dealing with mental disorders in remote areas, as is the case in India. In Kenya, community-based education campaigns have increased the number of mental health consultations by 30% in the last five years. This success shows that the integration of mental health services at the community level and increased public awareness can improve access and reduce the stigma that prevents people from seeking care.However, the results also highlight the need to strengthen public policy support and reduce stigma against mental health in the community to ensure the sustainability of programs that have been implemented.